Neoadjuvant chemotherapy with FLOT for locally advanced gastric cancer: A single-center experience from Vietnam - Duyen, Dinh Thi Hai; Tien, Vu Van; Lan, Nguyen Thi Mai (Tạp chí Nghiên cứu Y học, 2025)
Neoadjuvant chemotherapy (NACT) with the FLOT regimen (5-Fluorouracil, Leucovorin, Oxaliplatin, Docetaxel) has shown promising results for locally advanced gastric cancer (LAGC). This study aimed to evaluate the initial treatment outcomes of LAGC patients receiving neoadjuvant FLOT at Hanoi Oncology Hospital. A descriptive cohort study was conducted on 35 patients with LAGC (cT3-4 and/or cN2-3, M0) treated with neoadjuvant FLOT between October 2021 and February 2024. Clinical data, radiological and histopathological responses, surgical outcomes, and adverse events were retrospectively and prospectively collected and analyzed. The median age was 62 years, with a male-to-female ratio of 4.8:1. The majority presented with epigastric pain (80%) and tumors located in the antrum (68.6%). Among all patients, 91.4% were cT4 (62.8% cT4b), and 97.1% had lymph node metastasis on imaging. Thirty patients (85.7%) completed 4 FLOT cycles. Radiologically, 50% had partial response (PR), 43.3% had stable disease (SD), and 6.7% showed progression. Of the 32 patients who underwent surgery, 29 (90.6%) had radical resection with an R0 rate of 100%. Pathologic complete response (pCR) was observed in 6.7% of cases. The postoperative lymph node-negative rate (ypN0) was 25%. Neoadjuvant chemotherapy using the FLOT regimen demonstrated favorable disease control, enabling high R0 resection rates in patients with locally advanced resect able gastric cancer. These results support the use of FLOT in carefully selected Asian populations with LAGC, although further studies with larger sample sizes and long-term follow-up are warranted.